Teaching Learning Activities in Gurukul - Adhikari, Toya Nath (Pragya Darshan प्रज्ञा दर्शन, 2023)
The school understands that the teaching and learning of the students cannot be covered in the classroom and only by the curriculum. That is why the school has linked teaching and learning with the community and society. Every year, the school has been imparting various community-centered teaching and learning to the children in a way that integrates them with society. The methodology used for this study is related to interview, focus group discussions and observations to collect the information. The aim of this paper is to find out teaching learning activities which are used in Gurukul. The finding of this research article is that although teachers try to use the student centered methods, they use the teacher centered approaches mostly while teaching learning process.